Review of Centella asiatica (L.) Urban. - M Taghizadeh; N Yasa; A Naqinezhad; M Ahvazi (Institue of Medicinal Plants, ACECR, 2004)
AB-Boshghabi (Centella asiatica) from Apiaceae family, has been used as a traditional herbal medicine in Asiatic countries for hundreds of years. This plant is indigenous to the warmer regions of both hemispheres, including southeast Africa, Asia, Srilanka, the Pacific Islands, Madagascar, Eastern South America, Venezuela, Columbia. It is especially abundant in the swampy areas of India, Iran (around the Anzali lagoon), and Pakistan, Upto an altitude of approximately 700m. This hygrophyte plant is considered as a "vulnerable species" in the Red data book of plant species of Iran. This valuable hygrophyte species has a definitely exclusive habitat around the Anzali lagoon. The major principles are the triterpenes asiatic acid and madecassic acid, and their derived triterpene ester glycosides, asiaticoside and madecassoside. The major clinical indications for the use of centella asiatica in human include the treatment of wounds, venous insufficiency of the limbs, Certain mycobacterial infections and cellulitus. In the present article, we review mainly medicinal aspect of Centella asiatica that hitherto has not received much attention.